ORGANIZATIONAL COMMITMENT IN MEDIATING THE INFLUENCE OF WORK ENVIRONMENT AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Egi Ginanjar; Moh. Sutoro; Dadang Amiruddin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of the work environment and job satisfaction on employee performance with organizational commitment as a mediating variable at the Banten Province Energy and Mineral Resources Office. The study used a quantitative approach with a survey method. The study population was all employees of the Banten Province Energy and Mineral Resources Office, with a sample of 113 respondents determined using probability sampling techniques. Data collection was carried out by distributing questionnaires using a five-point Likert scale. Data analysis was carried out using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of the SmartPLS 4.0 application. The results showed that the work environment had a positive and significant effect on employee performance and organizational commitment. Job satisfaction had a positive and significant effect on organizational commitment, but did not have a significant direct effect on employee performance. Organizational commitment was proven to have a positive and significant effect on employee performance. In addition, organizational commitment was able to significantly mediate the effect of the work environment on employee performance and the effect of job satisfaction on employee performance. The research findings confirm that organizational commitment is a strategic variable in improving employee performance by strengthening the influence of the work environment and job satisfaction. Therefore, improving the quality of the work environment, job satisfaction, and strengthening organizational commitment need to be a priority in human resource management to support improving employee performance and organizational effectiveness at the Banten Province Energy and Mineral Resources Service.